KECEMASAN KELUARGA PASIEN RUANG ICU RUMAH SAKIT DAERAH SIDOARJO - Tripeni, Tripeni (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2014)
Anxiety is a state where the person experiences feelings of anxiety and activity in the autonomic nervous system responds to threats that are not clear and specific. Patient’s family that is caring in Intensive C are Unit (ICU) always feel anxiety. Because of that, family have to mixed up in the nursing care. The aim of this study was to indentify the anxiety that felt by the patient’s family in RSD Sidoarjo. The research used a descriptive design and take 30 people as samples. The result showed that only 43,3% family feel anxiety in average degress. Conclusions on this study it was found that the majority of respondents decreased anxiety after being given information on health, so nurses and other health workers are expected to cooperate with the cadres of health coaching in hospital.Key word: Axienty, Patients, ICU